IMPROVING STUDENTS’ READING ABILITY THROUGH PICTURE MEDIA DURING THE PANDEMIC PERIOD - Asran Asran (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The purpose of this study was to improve students’ reading skills at grade I by using picture media during the pandemic. This study was conducted by utilizing classroom action research involving 22 students. The results of this study showed that the average score of teachers’ activity in meeting I of Cycle I was 68 with good category, and it increased to 70 in meeting II with good category. Then, the average score of teahers’ activity in meeting I of Cycle II was 76.6 with good category, and it increased to 81.6 in meeting II with very good category. Moreover, the results of students activity showed that the average score in meeting I of Cycle I was 53.3 with adequate category, and it increased to 58.3 in meeting II of Cycle I with adequate category. Then, in meeting I of Cycle II, the average score of students’ activity was 65.8 with good category, and it increased in meeting II to 70.8 with good category. In addition, the students' reading skills were assessed by administering online tests individually which provided pictures. The results showed that the average score in Cycle I was 65.75, and the average in Cycle II was 70.6. This implied that the students’ reading comprehension ability increased for 7.37%. This study conculded that there was an increase in students' reading skills.